Amanita muscaria extract potentiates production of proinflammatory cytokines by dsRNA-activated human microglia - Wagner, Ashley; Pehar, Marcus; Yan, Zhimin; Kulka, Marianna (Frontiers in Pharmacology, 2023)
Recent interest in mushrooms and their components as potential therapies for mental health, along with recent government and health authority approvals has necessitated a more comprehensive understanding of their effects on the cellular microenvironment of the brain. Amanita muscaria has been ingested as a treatment for a variety of ailments for centuries, most notably those affecting the central nervous system and conditions association with neuroinflammation. However, the effects of these extracts on neuroinflammatory cells, such as microglia, are unknown. The effect of commercially-sourced A. muscaria extract (AME-1) on the human microglia cell line (HMC3) expression of surface receptors such as CD86, CXCR4, CD125 and TLR4 was determined by flow cytometry. AME-1 upregulated expression of all of these receptors. The effect of AME-1 on HMC3 production of IL-8 and IL-6 was determined and compared to tumor necrosis factor (TNF), polyinosinic-polycytidylic acid [poly(I:C)], substance P and lipopolysaccharide (LPS), all known activators of HMC-3 and primary microglia. HMC3 produced both IL-8 and IL-6 when activated with LPS, TNF and poly(I:C) but not when they were activated with substance P. Although AME-1 at higher concentrations increased IL-8 production of HMC3 on its own, AME-1 notably potentiated HMC3 production of IL-8 in response to poly(I:C). AME-1 altered expression of toll-like receptor 3 (TLR3) mRNA but not surface protein by HMC3. AME-1 also did not significantly alter expression of retinoic acid-inducible gene I (RIG-I) or melanoma differentiation-associated protein 5 (MDA5), both cytosolic sensors of dsRNA. Metabolomics analysis showed that AME-1 contained several metabolites, including the autophagy inducer, trehalose. Like AME-1, trehalose also potentiated HMC3 poly(I:C) mediated production of IL-8. This study suggests that Amanita muscaria extracts can modify HMC3 inflammatory responses, possibly due to their trehalose content.